2002
DOI: 10.1002/hlca.200290022
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactions of New Dithiolopyrroles

Abstract: Dedicated to Professor Dieter Seebach on the occasion of his 65th birthdayThe title compounds were prepared starting from pyrrolinone 4. Nucleophilic-displacement and ringclosure reactions yielded the dithiolopyrrole 5a, which formed salts with electrophiles (7, 8) as well as with bases. The crystal structure of 5a was determined. Oxidation of the dithioles 5a and 6a led to S(2)-oxides (10a, 11a) and the corresponding S(2)-dioxides (10b, 11b) depending on reaction conditions. The thiosulfinate 10a was converte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…) (Jiang et al ). Depending on the nature of R1, two dithiolopyrrolone groups are mainly distinguished: pyrrothins (R1 = CH 3 ) and holothins (R1 = H) that differ from each other by the side chain R2 (Stachel et al ). These compounds have been found to be produced by few species of actinobacteria ( Streptomyces and Saccharothrix ), Xenorhabdus and some marine bacteria such as Alteromonas rava , Photobacterium halotolerans , Yersinia ruckeri and Pseudoalteromonas sp.…”
Section: Introductionmentioning
confidence: 99%
“…) (Jiang et al ). Depending on the nature of R1, two dithiolopyrrolone groups are mainly distinguished: pyrrothins (R1 = CH 3 ) and holothins (R1 = H) that differ from each other by the side chain R2 (Stachel et al ). These compounds have been found to be produced by few species of actinobacteria ( Streptomyces and Saccharothrix ), Xenorhabdus and some marine bacteria such as Alteromonas rava , Photobacterium halotolerans , Yersinia ruckeri and Pseudoalteromonas sp.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, we have demonstrated that it is possible to activate a NÀS(O) bond in the pyrroloisothiazolone S-oxides 18a and 20a by oxidative addition of the Pt 0 complexes 24a ± c. The products isolated and characterized were the cis-amidosulfenato platinum(II) complexes 25 and 26a ± c. Compared with the analogous reactions of the isoelectronic 1,2-dithiolo [4,3-b]pyrrolone S-oxide (21) [14] …”
mentioning
confidence: 88%
“…Compound 1 was prepared as previously described in the literature. [35] Unfortunately, treatment of equimolar amounts of Fe 3 (CO) 12 and compound 1 in boiling THF for 3 hours does not afford the binuclear complex 2 (Scheme 1). In contrast, stirring a mixture of equimolar amounts of Fe 3 (CO) 12 and compound 1 in THF at 25°C followed by column chromatography afforded the binuclear complex 2 in moderate yield, as illustrated in Scheme 1.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%